2015
DOI: 10.1007/s13277-015-3549-1
|View full text |Cite
|
Sign up to set email alerts
|

Metformin use improves the survival of diabetic combined small-cell lung cancer patients

Abstract: Metformin has been reported having potential anticancer effect on kinds of solid tumors, but its role in combined small-cell lung cancer (C-SCLC) remains indistinct. This study aimed to explore whether metformin use has a prognosis benefit in diabetic C-SCLC patients. A total of 259 C-SCLC patients with diabetes were enrolled in our study. The clinicopathological parameters and survival data were collected and analyzed. The correlation between metformin use and clinicopathological characters was analyzed. Univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…All the included studies were reported in English. Of the 10 articles [1719, 2127], 1 described case-control design and 5 described cohort design involved Western region, and 4 described cohort design involved Asian region. Moreover, there were two publications focusing on SCLC, five on NSCLC, one on mixed cancers including SCLC and NSCLC, and two with unavailable information concerned.…”
Section: Resultsmentioning
confidence: 99%
“…All the included studies were reported in English. Of the 10 articles [1719, 2127], 1 described case-control design and 5 described cohort design involved Western region, and 4 described cohort design involved Asian region. Moreover, there were two publications focusing on SCLC, five on NSCLC, one on mixed cancers including SCLC and NSCLC, and two with unavailable information concerned.…”
Section: Resultsmentioning
confidence: 99%
“…Some, but not all [8] have reported improvements in progressionfree survival [9] and disease-free survival [10,11] but these investigations were limited by small sample sizes [8][9][10][11], drug exposure determined at limited numbers of time-points [8][9][10][11] and a lack of adjustment for important baseline patient characteristics [9]. Other studies have investigated metformin use and overall survival [12][13][14], but these results could reflect mortality from non-cancer causes.…”
Section: Introductionmentioning
confidence: 99%
“…A close examination of these studies revealed that these studies differed by timing of metformin exposure, population characteristics (cancer stage and histology), reference group, and adjustment for confounders. A study on small cell lung cancer reported improved survival 30 , but the time window of metformin use was unclear. In a study of 750 Stage IV NSCLC patients based on the SEER-Medicare data, pre-diagnostic metformin use was associated with significantly improved overall survival, after adjustment for tumor characteristics and chemotherapy 28 .…”
Section: Discussionmentioning
confidence: 99%